TRANSFORMATIONS OF PUBLISHING PRACTICES IN THE INFORMATIONAL CAPITALISM. THE CASE OF TESEO - Szpilbarg, Daniela (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
In the last decade there have been sharp reconfigurations in the publishing industry in Argentina. To begin with it is possible to think of three processes which coexist and mark the newest trends in the formation and configuration of the national publishing fields: industry concentration, the emergence of technologies and internationalization. This three processes are articulated and complementary transformative. In this context, the editors function as cultural brokers from the strengthening of a new type of projects that make innovative use of the possibilities of digitization of the word. The aim of this article is to expose the problem of digital publishing in the Argentine publishing field and how information technology and communication -ICTs- under the informational capitalism, generate new editors and editorial models offering digital forms of publication. In particular, we have analyzed the emergence, in 2007, of Teseo, from a qualitative perspective. On the one hand, the methodological approach was linked to the analysis of the website and its catalog. Two in-depth interviews were conducted with the director, Octavio Kulesz. Through inquiry by the sense that it operates as a propellant editor of cultural mediation process we will deepen in the direction of these new cultural processes.